A=5
How to do it:
30=6a
a=6/6 (Do on both sides) 30/6
a=(6/6 cancels out) 30/6
a=5
If 6a divided by 2 equals 12 then A equals
6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b
6a-3=8a+11 -3-11=8a-6a -14=2a a=-7
6a + 5a = -11 Combining like terms: 11a = -11 Dividing by 11: a = -1
2a*3 = 8+4a 6a = 8+4a 6a-4a = 8 2a = 8 a = 4
36
a + 6a - 9 = 30 7a - 9 = 30 7a = 30 + 9 7a = 39 a = 39/7 a = 5.571 (to 3 decimal places only).
26 = 30 - 6a Taking 30 off each side gives, 26 - 30 = -4 = -6a Dividing each side by -6 gives, -4 / -6 = a, thus a = 2/3 or 0.667
If 6a divided by 2 equals 12 then A equals
-6a + 8 = 2 -6a = -6 a = 1
To solve the equation 5a + 5 = 6a - 7, you first want to simplify both sides. Start by combining like terms on each side of the equation. Add 7 to both sides to isolate the variable terms on one side. Then, subtract 5a from both sides to solve for the variable a. The final answer is a = 12.
If you mean: 15a = 6a - 90 then the variable a works out as -10. If you mean 15a + 6a - 90, then it equals 21a - 90.
6a -12b + 30 = 6 (a - 2b + 5)
6a - 13 = -5 Therefore, 6a = 8 a = 8/6 a = 1.3 recurring (that is, 1.3333..)
If 6A - 58 = 44 then 6A = 102 making A = 17.
3(6a + 5) + 30 18a + 15 + 30 18a + 45
6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b